Farnesoid X receptor inhibits gankyrin in mouse livers and prevents development of liver cancer. Issue 3 (15th February 2013) - Jiang, Yanjun; Iakova, Polina; Jin, Jingling; Sullivan, Emily; Sharin, Vladislav; Hong, Il‐Hwa; Anakk, Sayee; Mayor, Angela; Darlington, Gretchen; Finegold, Milton; Moore, David; Timchenko, Nikolai A.
Abstract: One of the early events in the development of liver cancer is a neutralization of tumor suppressor proteins Rb, p53, hepatocyte nuclear factor 4α (HNF4α), and CCAAT/enhancer binding protein (C/EBP) α. The elimination of these proteins is mediated by a small subunit of proteasome, gankyrin, which is activated by cancer. The aim of this study was to determine the mechanisms that repress gankyrin in quiescent livers and mechanisms of activation of gankyrin in liver cancer. We found that farnesoid X receptor (FXR) inhibits expression of gankyrin in quiescent livers by silencing the gankyrin promoter through HDAC1‐C/EBPβ complexes. C/EBPβ is a key transcription factor that delivers HDAC1 to gankyrin promoter and causes epigenetic silencing of the promoter. We show that down‐regulation of C/EBPβ in mouse hepatoma cells and in mouse livers reduces C/EBPβ‐HDAC1 complexes and activates the gankyrin promoter. Deletion of FXR signaling in mice leads to de‐repression of the gankyrin promoter and to spontaneous development of liver cancer at 12 months of age. Diethylnitrosoamine (DEN)‐mediated liver cancer in wild‐type mice also involves the reduction of FXR and activation of gankyrin. Examination of liver cancer in old mice and liver cancer in human patients revealed that FXR is reduced, while gankyrin is elevated during spontaneous development of liver cancer. Searching for animal models with altered levels of FXR, we found that long‐lived Little mice have high levels of FXR and do not develop liver cancer with age and after DEN injections due to failure to activate gankyrin and eliminate Rb, p53, HNF4α and C/EBPα proteins. Conclusion : FXR prevents liver cancer by inhibiting the gankyrin promoter via C/EBPβ‐HDAC1 complexes, leading to subsequent protection of tumor suppressor proteins from degradation. (HEPATOLOGY 2013)